Implementasi Model Pembelajaran Team-Work dalam Meningkatkan Kemampuan Menangkap Makna Teks Prosedur Peserta Didik Kelas XII MIPA 3 Madrasah Aliyah Negeri 2 Ponorogo - Pratiwi, Winarni Dwi (Institut Agama Islam Riyadlotul Mujahidin Ngabar Ponorogo, 2020)
One of the learning activities is the process of transfer of knowledge from the teacher to the students. The implementation of learning English using the 2013 curriculum requires a number of fundamental changes. The first is the shift from the focus on the teacher (how to teach) to the focus on students (how to learn). The second is success in mastering the scientific field, not just understanding or aspects of knowledge but accompanied by basic life skills (skills) that are marked by changes in attitudes towards student learning achievement that increases. The formulation of the problem in this study are: Does the team work learning model can improve the ability to capture meaning in oral and written procedure text in the form of recipes in class XII.MIPA.3 Madrasah Aliyah Negeri 2 Ponorogo 2018/2019 Academic Year. In this study researchers collaborated with other teachers as well as with the school principal. The researcher is directly involved in the research from the beginning to the end of the study. Researchers try to see, observe, feel, appreciate, reflect and evaluate the learning activities that take place. The stages of the implementation of action research consist of planning, acting, observing, and reflecting. To get accurate research results, the data collected has been analyzed statistically using the mean or average formula. The criterion for success that marks the success of this study is the KKM (Minimum Completeness Criteria) which is a value of 75 that can be achieved by 80% of students. From the results of the study it was found that the average value in the cycle had a significant increase. Referring to the action hypothesis proposed in this class action research, it can be concluded that: there is an increase in the ability to capture meaning in the oral and written procedure text in the form of a recipe with a model of teamwork learning in class XII students. MIPA.3 Madrasah Aliyah Negeri 2 Ponorogo 2018 Academic Year / 2019.